Warsztat duetu autorskiego. O pisaniu kolaboratywnym Jolanty Fuchsówny i Jana Brzękowskiego - Wójtowicz, Aleksander; Boruszkowska, Iwona (Przestrzenie Teorii, 2021)
The article presents the concept of collaborative writing or multi-author writing using the example of the novel Black Paris by Jolanta Fuchsówna, a forgotten columnist of the “Ilustrowany Kurier Codzienny”, and the avant-garde poet and writer Jan Brzękowski. This interwar novel from 1932 is yet to be published in book form. The specificity of the preserved materials and the manuscript make the concept of collaborative writing the operative one for studying the text and describing these writers’ collaboration.